HUBUNGAN STATUS OBESITAS TERHADAP HIPERTENSI DI PUSKESMAS SUNGKAI KABUPATEN BANJAR - Zaleha, Zaleha (Politeknik Kesehatan Kemenkes Bengkulu, 2012)
Hypertension is becoming more prevalent in Indonesia.The risk of Hypertension increase with the development of obesity. A limited number of studies in Indonesia have examined relationship between obesity indicator and hypertension. The objective of the study conducted to know related between several obesity indicator and hypertension of patients at Sungkai Public Health Center in Banjar District. The study was observasional analityc with case control matched study. Subjects this study consisted of 60 subjects that were collected consecutively and devided into two group, case and control with comparison case and control 1 : 1. Blood pressure. Body Mass Index (BMI), Waist Circumference (WC) and Waist to Hip Ratio (WHR) were obtained, Chi Square Test or Fisher Exact Test was used to bivariate analitytic with α = 0,05. The Odds Ratio (OR) was calculated to predict the risk of each obesity indicator to hypertension.This study showed that BMI was significantly related with essensial hypertension in bivariate analysis (OR=3,1). The nonsignificant correlation (p > 0,05) identified for Waist Circumference and Waist Hip Ratio. Obesity indicator related to essential hypertension of patients at Sungkai Public Health Center in Banjar District was BMI